COMPARISON ANALYSIS OF THE CAPITAL STRUCTURE POLICIES OF FDI AND PMDN MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2018-2021 PERIOD - NURAZIZAH NURAZIZAH; AGUS MAULANA (MANKEU (JURNAL MANAJEMEN KEUANGAN), 2023)
This research done on the objects of PMA and PMDN manufacturing companies listed on the IDX. Made as decision-making regarding company risk and a consideration for investors in determining investment decisions. The population and sample used in this research are 20 manufacturing companies selected using purposive sampling, consisting of 10 PMA manufacturing companies and 10 PMDN manufacturing companies for the 2018-2021 period. The data was processed with the help of Microsoft Excel and then tested with the Independent Sample T-test via SPSS 23. The results showed that there was a significant difference between the Capital Structure of PMA and PMDN manufacturing companies as seen from the average DER results for PMA companies of 0.99 and PMDN companies 0.53 and the results of the Independent Sample T-test sig (2 Tailed) 0.000 are smaller than 0.05.